Pedagogical Design Patterns in Educational Mobile Apps: A Comparative Analysis of Learning Effectiveness across K-12, Higher Education, and Professional Training - Nguyen Thuy Van; Samer Yaghmour; Trinh Cong Son; Ngo Tat Hoat (International Journal of Interactive Mobile Technologies (iJIM), 2025)
Mobile learning applications have proliferated across educational contexts without systematic understanding of which pedagogical design patterns effectively support learning across different educational levels. This study developed a comprehensive pedagogical evaluation framework through systematic bibliometric analysis of mobile learning literature to identify design patterns and assess their effectiveness across K-12, higher education, and professional training contexts. Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines, we analyzed 53 documents (2006–2025) from Scopus using bibliometric techniques, network analysis, and thematic clustering to examine conceptual structures, collaboration patterns, and knowledge evolution. The analysis revealed fundamental fragmentation: while mobile learning demonstrates robust growth (9.89% annual increase) and dominates as the field’s organizing principle (betweenness centrality: 450.668), critical pedagogical concepts including instructional design, student engagement, and collaborative learning remain isolated with zero betweenness centrality. Educational level representation proved uneven (K-12: n = 9; higher education: n = 11; professional training: n = 5), with minimal comparative analysis across contexts. Ten distinct research clusters operated in isolation, with instructional design showing high internal consistency (density: 127.958) but minimal mainstream integration (centrality: 2.591). The predominance of short-term studies (60.4%) and limited international collaboration (15.09%) further constrains understanding of sustained impact and cross-cultural applicability. These findings expose a persistent technology-pedagogy divide undermining mobile learning’s educational potential, necessitating integrated frameworks that prioritize pedagogical design over technological innovation. Future research requires longitudinal investigations, systematic cross-level comparisons, and proactive examination of emerging technologies’ interaction with pedagogical principles to establish evidence-based guidelines for context-appropriate mobile learning design.